If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-15=-3x+13
We simplify the equation to the form, which is simple to understand
x-15=-3x+13
We move all terms containing x to the left and all other terms to the right.
+1x+3x=+13+15
We simplify left and right side of the equation.
+4x=+28
We divide both sides of the equation by 4 to get x.
x=7
| 6e^3x+4=9 | | 3G-22=-4-3g | | 16x^3-10x^2+14x= | | 4p^2-19p-5=0 | | 4(3e-2)=5(e+4) | | -4x+1=-47 | | 11t-13=3t-11 | | 3(4d-2)=5(3-d) | | 16-36-5= | | 28x^2-x-12=0 | | -22=x+-8 | | 6x+5=4-9 | | x+x+9+x+x+5=x+x+x+x+x | | 5(2a-6)=40 | | t-3/2=8/9 | | -25+25+4= | | 2(4x-3.1)=9x-6.2 | | t-3/3=8/9 | | -3+5x=-63 | | 6*11-8=72 | | E-6=-8 | | x^3-4x^2+4x-16= | | 2.7+0.6x=0.3 | | -6+6x=48 | | 1.25r+-7=2.5 | | 7+h=3 | | 39x-13= | | 100x-0.45=300x+0.75 | | 6.5-5k=-2.1 | | 5f-8=12 | | 3.9x+6-2.9x=1 | | 12a^2=a+1 |